Digital-Based Character Education Innovation for Shaping a Well-Characterized Indonesian Generation - Setiono, Joko; Kurniasih, Nia (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
The use of information technology as a learning medium reflects the process of modernization in education in Indonesia, aligning with the demands of the times and global developments. However, behind these benefits, there are risks that need to be addressed, such as the potential increase in demoralization among students. This concern is significant for educators, parents, and society as a whole. This article aims to analyze the strengthening of character education based on information technology as a significant innovation in the formation of a better national character. This study employs a qualitative approach with an in-depth literature review, analyzing research related to the utilization of information technology for character development among students. The findings indicate that the modernization of education through information technology can create more equitable and inclusive access to education, open new perspectives for educators and learners, and enhance the overall quality and meaning of education. Additionally, information technology accelerates the exchange of information, making it an effective means for strengthening student character. Information technology products provide a broad and engaging learning space, enabling students to share experiences, exchange information, and interact with experts. This supports the development of personal potential and character strengthening, allowing students to become more responsible and integral individuals. Penggunaan teknologi informasi sebagai media pembelajaran mencerminkan proses modernisasi pendidikan di Indonesia, yang sejalan dengan perkembangan zaman dan tuntutan global. Namun, di balik manfaat tersebut, terdapat risiko yang perlu diperhatikan, yaitu potensi peningkatan demoralisasi di kalangan pelajar. Hal ini menjadi perhatian penting bagi pendidik, orang tua, dan masyarakat. Artikel ini bertujuan untuk menganalisis penguatan pendidikan karakter berbasis teknologi informasi sebagai sebuah inovasi yang signifikan dalam pembentukan karakter bangsa yang lebih baik. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka yang mendalam, menganalisis kajian terkait pemanfaatan teknologi informasi dalam penguatan karakter peserta didik. Hasil penelitian menunjukkan bahwa modernisasi pendidikan melalui teknologi informasi dapat menciptakan akses pendidikan yang lebih adil dan inklusif, membuka perspektif baru bagi pendidik dan peserta didik, serta meningkatkan kualitas dan makna pendidikan secara keseluruhan. Selain itu, teknologi informasi mempercepat pertukaran informasi, menjadikannya sarana yang efektif untuk penguatan karakter peserta didik. Produk teknologi informasi memberikan ruang belajar yang luas dan menarik, memungkinkan peserta didik untuk saling berbagi pengalaman, bertukar informasi, dan berinteraksi dengan para ahli. Hal ini mendukung pengembangan potensi diri dan penguatan karakter, sehingga peserta didik dapat menjadi individu yang lebih bertanggung jawab dan berintegritas.